Decreased symptom burden following surgery due to support from an interactive app for symptom management for patients with pancreatic and periampullary cancer. (2nd September 2019) - Gustavell, Tina; Sundberg, Kay; Segersvärd, Ralf; Wengström, Yvonne; Langius-Eklöf, Ann
Abstract: Background: Patients with pancreatic and periampullary cancer have poor prognoses, experience multiple symptoms following surgery and sometimes lack knowledge of self-care activities. Consequently, it is vital to develop systems that support self-management, improvement of health-related quality of life and reduction of symptoms. Therefore, the aim was to evaluate the impact on health-related quality of life and self-care activity when using the Interaktor app following pancreaticoduodenectomy due to cancer. Material and Methods: Patients in the intervention group used Interaktor up to six months after surgery. They reported symptoms daily at home and received support for self-management by continuous access to written self-care advice and to their healthcare professionals. Descriptive data from the app were collected. Health-related quality of life and self-care activity were collected before surgery, and six weeks and six months after surgery. Comparisons between the intervention group ( n  = 26) and a historical control group ( n  = 33) were made. Decline/dropout rate was 37% in the intervention group and 10% in the control group. Results: Six weeks after surgery the intervention group rated significantly higher emotional functioning and less nausea/vomiting, pain, appetite loss, constipation, pancreatic pain, flatulence and worry about low weight. Twenty-five subscales/items showed non-statistical differences. Six months after surgery the intervention group rated significantly fewer hepatic symptoms, less worry about low weight, and higher self-care activity level. Thirty subscales/items showed non-statistical differences. The first four weeks, patients reported symptoms in a median 95% of the intended days, and for the rest of the period in median 83%. Conclusion: The use of an app for management of patient-reported outcomes reduces symptom burdens six weeks after pancreaticoduodenectomy due to cancer. Interaktor is well accepted for patients choosing to participate and appears to facilitate supportive care needs and timely symptom management for this patient group. Future studies should also include cost-benefits and objective measures.